Hambatan dan Model Dialog Keagamaan di Era Kontemporer - Muhammad In'am Esha (el Harakah: Jurnal Budaya Islam, 2008)
This paper examines problems of religious dialogues in this contemporary era. The conclusion of this discussion suggests that religious dialogue is one of the important problems in the globalization era that becomes one of the alternative methods to anticipate religious conflicts in our society. There are many barriers to develop religious dialogues, such as the level of knowledge, social-political problems, and psychological and theological barriers. In the recent era, three models of religious dialogue can be developed, that is, theological dialogue, anthropological dialogue, and cosmological dialogue. Makalah ini membahas masalah dialog keagamaan di era kontemporer ini. Kesimpulan dari diskusi ini menunjukkan bahwa dialog keagamaan merupakan salah satu masalah penting di era globalisasi yang menjadi salah satu metode alternatif untuk mengantisipasi konflik agama di masyarakat kita. Ada banyak hambatan untuk mengembangkan dialog keagamaan, seperti tingkat pengetahuan, masalah sosial-politik, dan hambatan psikologis dan teologis. Di era baru-baru ini, tiga model dialog keagamaan dapat dikembangkan, yaitu dialog teologis, dialog antropologis, dan dialog kosmologis.